The Public Service and Problem of Morale: Nigeria in Perspective - Ologunowa, Christopher Sunday; Itodo, Christiana Ijakuwa (NIU Journal of Social Sciences; Vol 3 No 2 (2017): KIU Journal of Social Sciences, Vol. 3 No. 2, September 2017, 2017)
The Public Service is viewed the world over as the Government on the spot or most demands and needs of a society. It is characterized as non-profit making but service oriented. The civil service forms the major or focal point of the public service in any society, and the symbolization is stronger even with the civil service in terms of bureaucracy. Many schools of thought accuse the civil service, most especially in the developing countries of inertia. Yet it is the main force of stability in terms of crisis and a powerful force for growth and change in normal times in any country. This paper takes a general global look at the nature, role and organization of the public service and the civil service in particular. An attempt was also made of examining the civil service in Nigeria and the problem of morale, performance and job satisfaction. In so doing, the author employs secondary method of generating data. The Government is known to be the largest employer in most societies of the world and most especially in developing nations. The government is the fastest growing employer and it is known that public employment expands as existing activities grow and new activities are undertaken. Usually, the choice between alternative proposals rests with ministers or commissioners, and once these duos have their final decisions. It is the duty of civil servants to implement them in the possible manner as if the decisions were their own. It is generally known that the morale of the civil service is therefore, a matter of the greatest importance to the government and all governments should as a matter of fact realize this. As long as members of the civil service carry out their duties diligently and in loyalty, honesty, and to the utmost of their capacity, one expects they should be given the full measure of protection by Government. Keywords:   Public Service, Civil Service, Morale, Loyalty.